Socio-Demographic Characteristics of the Hemophilia Patients - Uddin, Md Masum; Rahman, Md Mostafijur; Mehedi, ABM; Sabur, Md Abdus; Ali, Kh Mohammad; Akter, Shayla; Ahmed, Md Tanzim (Medicine Today, 2026)
Introduction with objective: In Bangladesh, hemophilia patients are not uncommon. Large numbers of haemophilia patients regularly attend in Hemophilia Treatment Center (HTC), Department of Haematology, and Dhaka Medical College Hospital for the management of disease and its complications. The aim of the present study was to assess the socio-demographic characteristics of the hemophilia patients. Materials and Methods: This observational study was carried out among 50 hemophilia patients at the Hemophilia Treatment Center (HTC), Department of Haematology, Dhaka Medical College Hospital (DMCH), and Dhaka from July 2019 to December 2019. Purposive sampling was done according to availability of the patients. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. Result: Majority of the respondents (38%) were less than or equal 5 years old beside 28% were 6 to 10 years old. 96% respondents were Muslim. 50% patients were unemployed and 46% were students beside only 4% were service holder. 52% patient’s economic status were middle class beside 28% were lower class and 20% were upper class. 92% patients had hemophilia A and 8% had hemophilia B. 68% had mild hemophilia, 24% had moderate and 8% had severe hemophilia. Conclusion: The present study revealed that most of the haemophilia patients belong to a middle socio-economic class, which can interfere their long-term adherence to the expensive therapy. Medicine Today 2026, Vol.38 (1): 82-84